2021
DOI: 10.3389/fpsyt.2021.747854
|View full text |Cite
|
Sign up to set email alerts
|

Affect Dysregulation in Context: Implications and Future Directions of Experience Sampling Research on Affect Regulation Models of Loss of Control Eating

Abstract: Loss of control eating is a core, transdiagnostic eating disorder symptom associated with psychological distress, functional impairment, and reduced quality of life. However, the factors that contribute to persistent loss of control eating despite negative consequences are not fully understood. Understanding the mechanisms that maintain loss of control eating is crucial to advance treatments that interrupt these processes. Affect regulation models of loss of control eating hypothesize that negative emotions tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…While NA is an established risk factor for dysregulated eating (Haedt‐Matt & Keel, 2011; Mikhail, 2021), less is known about factors that may buffer against the impact of NA. Negative emotions are not always avoidable, and it is important to identify resiliency factors that may prevent dysregulated eating even when NA is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NA is an established risk factor for dysregulated eating (Haedt‐Matt & Keel, 2011; Mikhail, 2021), less is known about factors that may buffer against the impact of NA. Negative emotions are not always avoidable, and it is important to identify resiliency factors that may prevent dysregulated eating even when NA is high.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, emotional eating (EE), or eating in response to NA, is a strong correlate and predictor of clinical binge eating (BE) (Ricca et al, 2009(Ricca et al, , 2012Stice et al, 2002). Associations between NA and dysregulated eating are observed not only at the between-person level, but also in within-person studies that track changes in NA and BE/EE over time (Haedt-Matt & Keel, 2011;Mikhail, 2021). In other words, not only are people with higher average NA more likely to experience BE/EE, but day-to-day or hour-tohour changes in NA may also amplify the risk for BE/EE.…”
Section: Introductionmentioning
confidence: 99%
“…Although past studies have observed a maladaptive stress response in adolescents with frequent LOC-eating prior to an episode of LOC-eating [ 27 , 28 ], our findings appear indicative of a healthful pre-meal stress response among youth with infrequent recent LOC-eating. This pattern of pre-meal stress responses may help to explain why prior studies have failed to detect a link among self-reported pre-meal negative affective states and LOC-eating in youth [ 6 , 11 , 12 , 13 , 54 ], despite consistent evidence for this relationship in adults with eating disorders [ 55 , 56 , 57 ]. Additionally, our findings are consistent with affective models of LOC-eating that are predicated on the notion that eating is used as a method to manage stressful circumstances, e.g., [ 8 , 9 , 10 ], thus potentially rendering a healthy stress response at early stages of disordered eating onset.…”
Section: Discussionmentioning
confidence: 89%
“…Additional limitations include the lack of specific consideration for certain factors that could influence ratings (eg, food insecurity); lack of items assessing muscularity-oriented behaviors and attitudes (of particular relevance for boys) and ARFID diagnostic criteria; and potentially variable psychometric performance of the measure across various subgroups of youth. Notably, numerous other measures/modalities are available for assessing ED symptomatology (eg, other interviews, 220–223 self-report questionnaires, 221 , 224 , 225 ecological momentary assessment protocols 226–228 ). As such, it is vital to consider the benefits and limitations of the various options in the context of one’s clinical or research aims, as well as in relation to the sociodemographic characteristics and identities of the person or persons who will be assessed.…”
Section: Discussionmentioning
confidence: 99%